A Healthy Family Home without Cigarette Smoke - Adrianto, Ratno; AR, Chaerunnisa; Lenik Gah, Regina; Nurlela, Siti; Maulana, Ady; 'Aina 'Uruba, Huurul; Lasari, Aramika; Pasha, Yuliana; Khalisha, Nailah (Mulawarman International Conference on Tropical Public Health, 2025)
Objective : The goal of this program is toincrease public knowledge and awareness about the dangers of smoking to one's own health and the health of the family, thereby preventing the occurrence of chronic diseases. Research Methods/ Implementation Methods : This program uses an extension method in the form of delivering material using PowerPoint, with the reading of pre-test questions (before the material) and post-test questions (after the material) to the community in Argomulyo Village. Results : The results of the PreTest and PostTest show an increase in knowledge after the counseling. Conclusion/Lesson Learned : This program can enhance the knowledge and awareness of both active and passive smokers regarding the impacts of smoking and the dangers of smoking indoors, so that smokers can make better decisions to quit smoking and create a healthier environment for themselves and those around them. Thus, this program contributes to efforts to maintain public health and reduce the risk of diseases caused by exposure to cigarette smoke.